Pengaruh Personal Hygiene dan Sanitasi Lingkungan terhadap Insidensi Scabies: A Literature Review - Rahma, Sitta; Bestari, Rochmadina Suci; Prakoeswa, Flora Ramona Sigit; Triastuti, N. Juni (Prosiding University Research Colloquium, 2022)
Background: Scabies is a skin infection due to an infestation caused by the female mite Sarcoptes scabiei varieta homini. Scabies is an infectious disease that is currently still difficult to cure, especially for someone living in an area with environment of massive dense population. Personal hygiene is an important risk factor in the incidence of scabies because the worse a person's personal hygiene level, the greater the risk of developing scabies disease was affected to human. This scabies can be transmitted in several ways, such as direct contact on the patient's skin by shaking hands and indirect contact with people affected by scabies, by wearing objects that have been used by the patient such as clothes or towels. Method: This research method is a literature review study. The technique of collecting data from search results using e-databases in the form of PubMed, Google Scholar, and Science Direct with the limitations of the last 10 years which will be eliminated according to the restriction criteria. Result: Based on the tests conducted, 1025 articles were found then screened according to the inclusion and exclusion criteria so that 20 articles were found. From all studies it was found that personal hygiene and environmental sanitation have an effect on the incidence of scabies. Conclusion: There is an influence of personal hygiene and environmental sanitation on the incidence of scabies. Keywords: Sarcoptes scabiei, Personal hygiene, Environmental sanitation.